STRATEGI KESANTUNAN BERBAHASA SUKU JAWA DALAM INTERAKSI ANTARSUKU DI HALMAHERA UTARA - Zain Syaifudin Nakrowi; Arifah Pujiyanti (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
Politeness Strategies in the Javanese Language in Interaction between Ethnicities in North Halmahera. This research was conducted to describe the perception of North Halmahera’s citizens towards the Javanese Ethnic’s speech politeness. The research strategy used was the qualitative research design which is assisted with quantitative design. The findings of this research show the scale of The Javanese Ethnic’s speech  politeness according to the perception of North Halmahera’s citizens which has been sorted in this following order: 1) apologizing, 2) sympathizing, 3) pleasantries, 4) avoiding disputes, 5) optimistic, 6) respectful, 7) not forcing, 8) indirect, 9) modesty, 10) jokes, 11) involving speech partners in speech activities, 12) native identity markers, and 13) presumptions.